ANALISIS DANA PERIMBANGAN DAN PAJAK DAERAH TERHADAP BELANJA LANGSUNG DI PROVINSI JAWA TIMUR 2015-2017 - Sasha Nadya Chairunnisa; M.Faisal Abdullah (Program Studi Ekonomi Pembangunan, 2019)
Abstract This research was aims to determine the contribution of balancing fund and local taxes on regional expenditure in East Java Province and to determine the effect of balancing funds and regional taxes on direct expenditure in East Java Province. The type of data used is secondary data, namely the realization of the regional budget for a period of 3 years, in 2015-2017 obtained from the website of the Directorate General of Fiscal Balance. The data analysis techniques of this study were panel regression analysis, contribution analysis and classic assumption test. Results analysis obtained by contribution of balancing funds to regional expenditure in quite high in each district and city in East Java Province. Regional tax contributions to regional expenditure are still low in every district and city in East Java Province. The results showed that balancing fund had a positive and significant effect on the district and city direct spending in East Java and the local tax also had a positive and significant effect on the direct spending of districts and cities in East Java Province.